2019
DOI: 10.1146/annurev-virology-092818-015803
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Human Parvoviruses: The Rocky Road to Fame

Abstract: Parvoviruses are structurally simple viruses with linear single-stranded DNA genomes and nonenveloped icosahedral capsids. They infect a wide range of animals from insects to humans. Parvovirus B19 is a long-known human pathogen, whereas adeno-associated viruses are nonpathogenic. Since 2005, many parvoviruses have been discovered in human-derived samples: bocaviruses 1–4, parvovirus 4, bufavirus, tusavirus, and cutavirus. Some human parvoviruses have already been shown to cause disease during acute infection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 154 publications
(307 reference statements)
0
31
0
Order By: Relevance
“…Adeno-Associated Viruses (AAVs) are small, non-enveloped viruses that hold great promise as gene therapy vectors [1]. AAVs belong to the genus dependoparvovirus ,in the family Parvovirinae (for reviews, [2][3][4]). The model species is dependoparvovirus A, of which the prototype strain is AAV2.…”
Section: Introductionmentioning
confidence: 99%
“…Adeno-Associated Viruses (AAVs) are small, non-enveloped viruses that hold great promise as gene therapy vectors [1]. AAVs belong to the genus dependoparvovirus ,in the family Parvovirinae (for reviews, [2][3][4]). The model species is dependoparvovirus A, of which the prototype strain is AAV2.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the PARV4 sequences in two PARV4‐DNA positive source plasma pool samples were genotyped and the results demonstrated that at least two PARV4 genotypes, 1 and 2, were currently present in China. No genotype 3 was detected, which was not unexpected since this genotype was reported to be endemic in Ghana 16 . Besides, the possibility that genotype 3 might be present at an extremely low level in the sample, and, therefore, escaped identification can not be completely ruled out.…”
Section: Discussionmentioning
confidence: 70%
“…All these three genotypes have been detected in human blood or blood products although they seem to have different epidemiology. Genotypes 1 and 2 are prevalent in North America, Europe, and some countries in Asia while genotype 3 seems to be endemic in Ghana 16 . However, data on the existence of different PARV4 genotypes circulating in Chinese plasma donors are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parvoviruses are small, non-enveloped viruses (for reviews, see [1][2][3]). We will focus on two in particular: human parvovirus B19 (B19V) and human parvovirus 4 (PARV4).…”
Section: Introductionmentioning
confidence: 99%